Distance and eccentricity based invariants of windmill graph. (3rd October 2019) - Kang, Shin Min; Hashim, Imran; Ahmad, Haseeb; Kwun, Young Chel
Abstract: In the fields of chemical graph theory, molecular topology, and mathematical chemistry, a topological index also known as a connectivity index is a type of a molecular descriptor that is calculated based on the molecular graph of a chemical compound. In this paper, we computed the Hosoya polynomial, Wiener index and hyper Wiener index of Windmill graph. We also computed Harary polynomial, Schultz polynomial, modified Schultz polynomial, eccentric connectivity polynomial, generalized Harary index, multiplicative Wiener index, Schultz index, modified Schultz index, eccentric connectivity index, etc for understudy families of graphs.